Pemanenan Air Hujan Secara Komunal Di Desa Teluk Papal Kecamatan Bantan Kabupaten Bengkalis - M. Rizki E. Janrosl; Bambang Sujatmoko; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Providing clean water is a major concern, because water is a basic need and is essential for life and health of mankind. Rainwater is a source of high quality water which is available every rainy season and has the potential to reduce the pressure on the use of fresh water resources (fresh water sources). Rainwater coming from the roof of the house is usually the cleanest water alternatives that can be used as a source of clean water one of them in the village of Teluk Papal, Bantan District, Bengakalis Regency. This study aims to find out alternative clean water that can be used in the village and determine the volume of rain water storage and rainwater harvesting design plan or Rain Harvesting. In this research, modeling Rain Cycle 2 is a rainwater harvesting modeling that uses some of the data, the data are derived from primary data adn secundary data in the form of extensive data roofs society, data on water requirements based on the number of family members , and the data of showers field. The results of this study rainwater harvesters with a communal system using a tank capacity of 14 m3 in Teluk Papal village. The rain harvesting in communal system gives a large percentage of fulfillment where the storage volume can be planned optimally to fulfill the needs of clean water.Keywords : Rain Harvesting, Rain Cycle 2, Communal System